Characterizing the trophic ecology of herbivorous coral reef fishes using stable isotope and fatty acid biomarkers - Rita García-Seoane; W. Lindsey White; Brett M. Taylor; Kendall D. Clements (PLoS ONE, 2025)
Understanding the trophic ecology of herbivorous and detritivorous fishes is essential for evaluating their ecological roles in coral reef ecosystems. In this study, we combined bulk stable isotope (δ15N and δ13C) and fatty acid analyses to investigate trophic partitioning and dietary resource use among herbivorous and detritivorous fishes from the Great Barrier Reef, Australia. Isotopic niches and fatty acid profiles confirmed significant trophic partitioning among algivores, detritivorous surgeonfishes, and parrotfishes. We also applied mixing models based on these ecological tracers to quantify the contributions of basal dietary sources to the fish. Our findings further support previous dietary knowledge for several species, including algivorous acanthurids, kyphosid chubs, and the rabbitfish Siganus doliatus. However, they also highlight trophic niche specializations within these groups, particularly in Naso unicornis, which assimilates substantial dietary protein from epiphytic cyanobacteria despite a macroalgal diet, and in the detritivorous Ctenochaetus striatus, which exhibited isotopic similarities to parrotfishes but differed in fatty acid composition, likely due to a higher intake of diatoms. Additionally, our analyses reinforce the distinctive dietary composition of parrotfishes, emphasizing the complexity of their feeding biology, in which microscopic photoautotrophs such as cyanobacteria and dinoflagellates play a key dietary role that has often been overlooked in previous studies on their nutritional ecology. Furthermore, these findings underscore the usefulness of multi-tracer approaches in refining our understanding of coral reef fish trophic ecology.